Dead in the water - Marrs, John (Freelance journalist) (Thomas & Mercer, 2026)
After surviving a near-drowning, Damon experiences vivid memories of his life, including one unfamiliar and disturbing image of a dead boy. Unable to account for this memory, he becomes increasingly preoccupied with uncovering its origin. As Damon investigates his past, he begins to believe that recreating near-death experiences may allow him to recover the missing memory. His search leads him to form an alliance with a stranger who assists him in this pursuit, raising questions about memory, identity, and the consequences of confronting unresolved truths.